HASSAN HANAFI’S OCCIDENTALISM - Ridho Al-Hamdi (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
This paper examines Hanafi’s concept of Occidentalism in the epistemological approach. It aims to investigate the character, study source, research method, validity, and objectives of Occidentalism. The paper findings demonstrate that Occidentalism is a science which aims to dismantle the myth of Western superiority and, in turn, to build an equal civilization. The study root of Occidentalism is the formation, structure, and fate of the European consciousness. The formation comprises the exposed and unexposed sources of the European consciousness. The structure encompasses the ideologies of nationalism, Zionism, Nazism, Facism, and racialism. Fate relies on the model of the relationship between the East and the West. Afterward, Hanafi employs two research methods: historical-dialectical and phenomenology. Lastly, science can be recognized as Occidentalism if it has a fivefold standard: there is the dialectic of the East and the West, positioning European consciousness as the study object, self-liberation as the spirit to liberate the East from Western hegemony, dismantling the myth of cosmopolite culture, and the accomplishment of an equal civilization.